Worth and Competitiveness in Spain’s Furniture Sector - Maldonado Guzman, Gonzalo (Mercados y Negocios, 2016)
This paper has as main objective to analyze the effects of the manager’s worth in the competitiveness of the Spain furniture sector. The empiric analysis was done on a sample of 322 furniture producing companies in Spain with twenty or more employees. The results show the experience, abilities and the education have a positive impact in the manager’s performance. Also, the performance has a positive impact in the manager’s worth and this has a positive impact in the competitiveness of the companies that integrate the furniture sector